While the previous answers are all fine and pretty, they all take up too much space for my liking!
So I've come up with a tidier solution in C:
a = (b - a) + (b = a);
It doesn't work with strings, but both integers and floating points work just fine.
It works like so:
int a = 5, b = 7;a = (b - a) + (b = a);/* turns into */a = (7 - 5) + (b = 5);/* b is now 5 */a = 2 + 5;/* a is now 7 */
The key here is the order at which expressions are parsed (left to right). Because of that, the first occurrence of b in the expression is replaced by b's original value, and only after that is b assigned to a.
I realize that this is an old and already answered question, but perhaps this will be useful to someone out there